Lipid disequilibrium destabilized a subset of membrane proteins - Chaw, Rui Jie (2016)
Imbalance between the major membrane phospholipids, phosphatidylcholine and phosphatidylethanolamine, has been implicated in several disease states. In yeast cells under membrane lipid disequilibrium, protein levels of Sbh1, a subunit of the Sec61 translocon complex, is decreased. A MYTH screen for protein-protein interaction showed interaction between Sbh1, Sec61 and Sss1 in wild type cells but not under lipid disequilibrium. To validate the results of the MYTH, a co-immunoprecipitation approach was taken to verify the interaction of Sbh1, Sec61 and Sss1 in wild type and under lipid disequilibrium. Results from the Co-IP showed interaction of Sbh1 and Sec61 in wild type and Δopi3 cells. Furthermore, the MYTH showed interaction of Sbh1 with Doa10 under lipid disequilibrium. Thus, the degradation mechanism of Sbh1 was investigated. Results from a cycloheximide chase assay showed that a K41A mutation in Sbh1 stabilizes the protein under lipid disequilibrium, thereby suggesting K41A is recognized for degradation under lipid disequilibrium. Additionally, membrane fluidity is suggested to play a role in Sbh1 stability. To investigate this, the sole fatty acid desaturase in yeast, Ole1, was overexpressed as a model of increased membrane fluidity. Using a cycloheximide chase assay, the overexpression of Ole1 was found to decrease the stability of Sbh1.